1982
DOI: 10.1037/0022-006x.50.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Are hypertensives less assertive? A controlled evaluation.

Abstract: In the psychosomatic literature hypertension has frequently been associated with an inability to express emotions, especially those emotions involving conflict. The present study was designed to directly assess the performance of hypertensive patients in increasingly demanding interpersonal interactions. Twelve extended role-played scenes incorporating the expression of positive and negative emotional states were employed in the study. Behavioral, physiological, and subjective ratings were obtained. Performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This implies an unusual constriction of the capacity to behave assertively, which is determined almost entirely by AD, rather than by more relevant or appropriate contin gencies. Our findings in this regard comple ment those of Keane et al [15], who com pared the assertive behaviour during role play of matched hypertensive patients, normotensive medical outpatients, and normal subjects. Both the hypertensive patients and the medical outpatients were rated as signif icantly less assertive during role play than the normal subjects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This implies an unusual constriction of the capacity to behave assertively, which is determined almost entirely by AD, rather than by more relevant or appropriate contin gencies. Our findings in this regard comple ment those of Keane et al [15], who com pared the assertive behaviour during role play of matched hypertensive patients, normotensive medical outpatients, and normal subjects. Both the hypertensive patients and the medical outpatients were rated as signif icantly less assertive during role play than the normal subjects.…”
Section: Discussionsupporting
confidence: 88%
“…In our own study, asser tion abnormalities were revealed primarily through the unusual association of two sepa rate measures, namely AD and AB. Keane et al [15] suggested that assertion abnormali ties in hypertensive patients reflected a 'chronic illness syndrome', rather than hy pertension per se. This view accords with our own findings, which imply that the con cept o f 'chronic illness syndrome' should be extended to include the patient's spouse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aware hypertensives have not been found to differ from medical and surgical patients (4), ulcer patients and general illness patients (10), chronically ill outpatients (74), normotensive patients attending a general medical clinic (11,17,21), cardiovascular disease patients (12), or patients with secondary hypertension (13,15). The conclusion based upon these studies, taken together, may be that the influence of disease knowledge on personality parameters is a general phenomenon which is associated with many different medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the earlier empirical literature concluded that neuroticism (2), hostility, and difficulties in coping with anger were associated with hypertension (3). However, much of this work suffers from major methodological flaws, including inadequate methods to diagnose hypertension and the use of unvalidated measures of personality, and is confounded by the recruitment of subjects from hypertension treatment centers and the use of antihypertensive medications (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Moreover, little attention has been given to the importance of differential exposure to medical attention and hypertension labeling as determinants of personality.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been over 50 years since Alexander (1939) first proposed what he termed the "suppressed hostility" hypothesis, suggesting that hypertensive patients were characterized by strong dependency needs and hostile impulses, firm conclusions about the role of anger expression in essential hypertension have yet to be elucidated. Some investigations have shown hypertensives to be more submissive in interpersonal situations in contrast to normal blood pressure controls (e.g., Gentry et al, 1982;Keane et al, 1982), while others have found patients with high blood pressure to be more aggressive than normotensive controls (e.g., Baer et al, 1979;Schachter, 1957). Although the exact nature of this relation has not been established, existing data support the commonly observed link between lack of anger expression skills (i.e., assertiveness) and problems of blood pressure control (e.g., Harburg et al, 1979).…”
Section: Introductionmentioning
confidence: 99%